MAPPING SHARIA GOVERNANCE MATURITY IN INDONESIAN GENERAL TAKAFUL: AN ACTOR-NETWORK THEORY ANALYSIS OF FOUR CASES - R. Melda Maesarach; Euis Amalia; Desmadi Saharuddin; Suhendra (Referensi Islamika: Jurnal Studi Islam, 2026)
Indonesia's general takaful industry faces intensifying regulatory pressure the UU 40/2014 spin-off mandate and POJK 20 and 23/2023 capital requirements yet sharia governance maturity remains uneven across firms. This study addresses the absence of an empirical, network-based account of how governance matures across companies with different ownership structures. A qualitative multiple case study examined four full-fledged general takaful firms representing distinct ownership structures (state-owned, regional state-owned, private national, and joint venture). Nine in-depth interviews with directors, Sharia Supervisory Board (DPS) members, and senior managers were analysed using Braun and Clarke's (2006) thematic analysis integrated with Callon's (1986) four moments of translation. Maturity was scored on a five-point Likert scale across nine SGM constituents and aggregated via the Corporate Governance Maturity Index formula (Imat) of Vidal et al. (2012), with scores triangulated against annual reports, governance reports, DPS reports, and audit reports for 2019–2024. NVivo 14 supported the coding. Six cross-case themes emerged from the four cases studied. The industry-aggregate Imat reached 2.0022, situating the sample at Level 3 (Regulated/ Normalized), but three of four firms individually remained at Level 2. Within this sample the SGM network appears semi-stable with partial translation: problematisation reaches compliance but not maturity; interessement succeeds for compliance but is limited for maturity; the DPS tends to function as a constrained obligatory passage point; and certified sharia auditors, formal sharia audit frameworks, and sharia IT monitoring systems are absent across the four firms studied—missing actors that, in this sample, fragment the network. The private national pioneer (PT. C) recorded the highest maturity, inverting the institutional-pressure expectation that BUMN status would yield the highest score. Findings are bounded by the four-firm scope and Indonesia's regulatory context; transferability to life takaful or to sharia units yet to complete spin-off is not claimed. Implications include the need for a maturity-based regulatory instrument, DPS competence reforms integrating business and finance expertise, a formal sharia audit framework, and standardised sharia IT monitoring mechanisms. This is the first study to integrate Actor-Network Theory with sharia governance in Indonesian takaful and to operationalise SGM as a nine-constituent extension of Corporate Governance Maturity, contributing both methodologically and conceptually to Islamic finance scholarship.